2019
DOI: 10.1111/trf.15435
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen reduced plasma products: a clinical practice scientific review from the AABB

Abstract: BACKGROUND A small body of literature assessing the efficacy and safety of pathogen reduced (PR) plasma has been published. STUDY DESIGN AND METHODS An AABB committee systematically reviewed the literature and graded the clinical trial evidence with the assistance of a GRADE expert. RESULTS Most studies identified were low quality and had a small sample size; in addition, efficacy and safety were monitored in many different ways making it difficult to quantify therapeutic benefit and risk. The data analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Plasma, for the first time treated with solvent detergent (S/D) was used in Europe in 1992 and only six years later, in North America (54).…”
Section: Pi Technologies For Plasmamentioning
confidence: 99%
“…Plasma, for the first time treated with solvent detergent (S/D) was used in Europe in 1992 and only six years later, in North America (54).…”
Section: Pi Technologies For Plasmamentioning
confidence: 99%
“…Preventive blood transfusion is mainly performed before surgery or invasive procedures, and a large volume of trial data suggest that the use of FFP in many patients is only indicated when major bleeding occurs. For all individuals born after January 1, 1996, pathogen-inactivated plasma is recommended because the associated risk of infection with known test viruses is very low [5,6]. The safety of blood donation has been improved through quarantine, but due to the incubation period of potential pathogens, there is still a risk for infection transmitted by blood transfusion.…”
Section: Introductionmentioning
confidence: 99%